ADHD among incarcerated youth: An investigation on the congruency with ADHD prevalence and correlates among the general population - Gordon, Jill A. (American journal of criminal justice, 2005)
The limited literature on the topic speculates that the rate of ADHD would be higher among incarcerated youth than found in the general population. However, to our knowledge no such published figures exist for juveniles in the United States. This study investigates the likelihood of ADHD diagnosis among 453 incarcerated youth and compares and contrasts a variety of demographic, social, educational, psychological, and criminal characteristics to the general literature on ADHD. Both similarities and differences are reported.